Diagnosis and management of Crohn’s disease in retarded child - Rahmi Amtha (Dental Journal (Majalah Kedokteran Gigi), 2009)
Background: Crohn’s disease is an uncommon condition characterized by granulomatous lesions. It is a rare disease and affects mainly in the terminal ileum. It may also manifest in the oral cavity as an unhealed, painful chronic apthous-like ulcer and may be undiganosed, so that it leads to the mismanagement of the disease. Purpose: To overview the establisment and managment of a retarded child with chronic painfull ulcers and gastrointestinal problems. Case: An 11-year-old retarded child who complained of ulcers since 6 months ago on the both side of the cheek and the lateral border of the tongue. Large irregular lesions were found accompanied by lips swelling, gingival hyperplasia, mucosal tags, hypersalivation. The blood test showed that the patient was suffering from anemia and haematinic (Fe, Folat and vitamin B12) deficiencies. Weight loss occurred for last 6 months, abdominal pain and constipation were also identified. Daily food pattern showed imbalance food intake. Histopathology features showed granolumatous lesions and was confirmed as a Crohn’s disease. Case management: Reassurance and team work with gastroenterologist were performed. Systemic sulfasalazin combined with corticosteroid and multivitamin were administered. Oral hygiene was maintained with hyaluronic acid mouthwash. Reduced in size of ulcer, pain and swelling were shown gradually. Oral ulcers and gastrointestinal symptoms disappeared after 2 months treatment. Conclusion: Diagnosis of Crohn’s disease needs a comprehensive clinical examination and histopathological test are mandatory to be able to manage the disease thoroughly.